The Effect of Addition of Pridot Leaf Extract and Juice of Red Watermelon Albedo on Carbonated Coconut Drink of Blood Glucose Levels of Mice - Cindy Puteri Utami Barus; Elisa Julianti; Era Yusraini (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2019)
In this study, the effect of addition of pirdot leaf extract and juice of red watermelon albedo oncarbonated coconut drink of blood glucose levels was done by giving samples orally to mice. This study used 30white male wistar mice, which were divided into 6 treatment groups that containing 5 mice in each group i.e:normal untreated mice given with aquades (negative control), diabetic untreated mice given with aquades(positive control), normal mice treated with 0.6 mL per 27 g bw per day of carbonated coconut drink, diabeticmice treated with 0.6 ml per 27 g bw per day of carbonated coconut drink, normal mice treated with 0.6 mL per27 g bw per day of commercial soda, and diabetes mice treated with 0.6 mL per 27 g bw per day of commercialsoda. The treatment was carried out for 14 days and observations made on blood glucose levels and body weightof mice. The results showed that giving of carbonated coconut drink by adding pirdot leaf extract and juice ofred watermelon albedo had a highly significant effect on blood glucose levels of mice. The effect washypoglycemic effect, which can reduce blood glucose levels on the diabetes group about 6,536%, while on thenon-diabetic group about 3,316%. However, the giving of commercial soda provides a hyperglycemic effect thatincreased blood glucose levels about 19,787% on the diabetic group, while on the non-diabetic group about12,750%. In addition, giving of carbonated coconut drink by adding pirdot leaf extract and juice of redwatermelon albedo had a highly significant effect on the body weight of mice. The effect was weight gain on thediabetes group about 4,171%, while on non-diabetics about 2,564%. However, giving commercial soda had aweight loss effect about 33,750% on the diabetic group, while on the non-diabetic group about 6,884%.